The connection of menarche between sportswomen and their mothers - Nikoloska K.; Shukova Stojmanovska D. (Faculty of physical education, sport and health, 2018)
The aim of the research is to determine whether there is difference in the age at menarche between daughters and their mothers, whether there is difference in terms of discomfort which is related to training (before, during and after menstruation) and whether there is mitigation of the menstrual symptoms among sportswomen who train actively in comparison to the period when they did not train actively. The research has been carried out on sportswomen from the Judo Club “Pujanke” from Split, Croatia, at the age from 12 to 17 (+/- 6 months) and their biological mothers. Two anonymous closed type questionnaires were given to the respondents. The first questionnaire consisting of 19 questions was given to the sportswomen and the second one consisting of 18 questions was given to their mothers. The questionnaire which was given to the sportswomen included questions about their menarche and the symptoms, and questions about their physical activity. The questionnaire which was given to their mothers had instructions on how to answer the questions; the questions should be answered in two ways: for ‘the past’ and for ‘today’. ‘The past’ refers to the period when the mothers were the same age as their daughters are today. The questionnaire includes questions about their menarche and the symptoms, and questions about their physical activity in the past and today. In the research, the ratio is calculated with χ2 test for both samples, as well as their representation in terms of frequency for each question. From the results, we can conclude that the average age at menarche among sportswomen is 12, regarding their mothers, for almost half of them, the age at menarche is 12 and 14. 46.67% of the sportswomen do not experience painful menstruation, therefore 93.33% attend training during menstruation. Only a small percentage of the respondents wrote that the discomfort and the menstrual bleeding affected their competition results.
Keywords: menarche, questionnaire, sportswomen, judo, χ2 test